The Engaged to Innovate: Exploring The Impact of Workload, Training, and Work Discipline In Driving Innovative Performance Through Employee Engagement - Titi Sari, Retno; Hadi, Syamsul; Subiyanto, Didik (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
This research aims to analyze the impact of workload, training, and work discipline on the innovative performance and employee engagement of Yogyakarta City's Regional Revenue Division staff. It also examines how Employee engagement modifies the connection between these factors and innovative performance, addressing gaps in understanding their effects on engagement and innovation. As many as eighty personnel of the Regional Revenue Division of the BPKAD in Yogyakarta City were included in the collection of data for this study, which utilized the Non-Probability sample model as the sample technique. For the purpose of this study, primary data was collected through the administration of questionnaires. This study employs the tools of data analysis, namely Partial Least Square (PLS) is a variance-based structural equation model (SEM) and the software SmartPLS Version IV. The research findings reveal that workload and work discipline does not influence innovative performance, while training positively impacts innovative performance. Workload also has no effect on employee engagement; however, training and work discipline positively influence employee engagement. Furthermore, employee engagement positively affects innovative performance. It mediates the beneficial impact of training on innovative performance, but it does not mediate the association between workload and innovative performance. Employee engagement is not a mediator for the impact of work discipline on innovative performance. This research contributes to human resource management theory by examining how employee engagement mediates the relationships between workload, training, work discipline, and innovative performance. It supports existing literature by highlighting the key role of engagement in linking these factors to innovation outcomes.